Being a Participant Matters: Event-Related Potentials Show That Markedness Modulates Person Agreement in Spanish - Alemán Bañón, José; Rothman, Jason (Frontiers in Psychology, 2019)
The present study uses event-related potentials to examine subject-verb person agreement in Spanish, with a focus on how markedness with respect to the speech participant status of the subject modulates processing. Morphological theory proposes a markedness distinction between first and second person, on the one hand, and third person on the other. The claim is that both the first and second persons are participants in the speech act, since they play the speaker and addressee roles, respectively. In contrast, third person refers to whomever is neither the speaker nor the addressee (i.e., it is unmarked for person). We manipulated speech participant by probing person agreement with both first-person singular subjects (e.g., yo…lloro “I…cry-1ST-PERSON-SG”) and third-person singular ones (e.g., la viuda…llora “the widow…cry 3RD-PERSON-SG”). We also manipulated agreement by crossing first-person singular subjects with third-person singular verbs (e.g., yo…*llora “I…cry 3RD-PERSON-SG”) and vice versa (e.g., la viuda…*lloro “the widow…cry 1ST-PERSON-SG”). Results from 28 native speakers of Spanish revealed robust positivities for both types of person violations, relative to their grammatical counterparts between 500-1000ms, an effect that shows a central posterior distribution, with a right-hemisphere bias. This positivity is consistent with the P600, a component associated with a number of morphosyntactic operations (and reanalysis processes more generally). No negativities emerged before the P600 (between 250-450ms), although both error types yielded an anterior negativity in the P600 time window, an effect that has been argued to reflect the memory costs associated with keeping the errors in working memory to provide a sentence final judgment. Crucially, person violations with a marked subject (e.g., yo…*llora “I…cry 3RD-PERSON-SG”) yielded a larger P600 than the opposite error type between 700-900ms. This effect is consistent with the possibility that, upon encountering a subject with marked features, feature activation allows the parser to generate a stronger prediction regarding the upcoming verb. The larger P600 for person violations with a marked subject might index the reanalysis process that the parser initiates when there is a conflict between a highly expected verbal form (i.e., more so than in the conditions with an unmarked subject) and the form that is actually encountered.